2012
DOI: 10.3354/meps09601
|View full text |Cite
|
Sign up to set email alerts
|

Diet of a specialist in a changing environment: the crabeater seal along the western Antarctic Peninsula

Abstract: Although crabeater seals Lobodon carcinophaga are among the most abundant consumers of Antarctic krill Euphausia superba, their diet has rarely been studied throughout most of the species' range. Using δ N values. The median (with range) contribution of Antarctic krill to the diet of crabeater seals, as estimated using the Bayesian mixing model MixSIR, was 87.9% (81.2 to 94.8%). During 2002, krill biomass in the wAP was at one of its lowest levels during the last 2 decades, coinciding with a slight reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 89 publications
4
48
0
Order By: Relevance
“…, Hückstädt et al . ). SIA is particularly useful for detecting temporal variation in diet because different tissues record ecological information over a variety of time scales from weeks ( e.g ., blood plasma) to months ( e.g ., red blood cells) and years ( e.g ., bone collagen) (Martínez del Rio et al .…”
mentioning
confidence: 97%
“…, Hückstädt et al . ). SIA is particularly useful for detecting temporal variation in diet because different tissues record ecological information over a variety of time scales from weeks ( e.g ., blood plasma) to months ( e.g ., red blood cells) and years ( e.g ., bone collagen) (Martínez del Rio et al .…”
mentioning
confidence: 97%
“…In contrast, the half-life of an isotopic tracer injected in captive harbour seals Phoca vitulina, was 47.1 days (Zhao & Schell 2004), although isotopic changes were visible after four days which implies that the marker incorporates rapidly into the protein synthesis of the growing vibrissae (Hirons et al 2001). As a result, vibrissae are increasingly utilised to study the diet of pinnipeds (Greaves et al 2004;Hückstädt et al 2011Hückstädt et al , 2012Newland et al 2011;Hindell et al 2012;Walters et al 2014). Nevertheless, the vibrissal growth rates of several phocid species remain to be determined, despite the recent interest in the utilisation of vibrissae to increase the temporal resolution of the dietary data (e.g., Hirons et al 2001;Greaves et al 2004;Zhao & Schell 2004;Hall-Aspland et al 2005;Beltran et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, such a combined approach requires higher resolution SI data (Beltran et al 2015; also see Banks et al 2014). The SI signature captured along the length of keratinous tissue, such as feathers (Grecian et al 2015), nails, hair or vibrissae, provides a time-series of the species' dietary history, if analysed chronologically (Hückstädt et al 2012;Robertson et al 2012;Walters et al 2014;Beltran et al 2015). Numerous studies focussed on ascertaining the exact, species-and tissue-specific growth rates of slow-growing, biologically inert keratinous tissue of various species in different habitats (e.g., Greaves et al 2004;Rohwer et al 2009;Beltran et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that seals often frequented the sites of MCDW penetration in troughs (Goetz et al, 2012). It is likely that this represents the presence of certain food items in the water mass, specifically Euphausia superba, Antarctic krill, which occur in waters off the shelf and whose subadult stages appear to be associated with intrusions (Piñones et al, 2013).…”
Section: The Ross Seamentioning
confidence: 93%